2011
DOI: 10.1186/1742-2094-8-163
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional expression patterns of α-synuclein, TNF-α, and IL-1β; and variable status of dopaminergic neurotoxicity in mouse brain after Paraquat treatment

Abstract: BackgroundParaquat (1, 1-dimethyl-4, 4-bipyridium dichloride; PQ) causes neurotoxicity, especially dopaminergic neurotoxicity, and is a supposed risk factor for Parkinson's disease (PD). However, the cellular and molecular mechanisms of PQ-induced neurodegeneration are far from clear. Previous studies have shown that PQ induces neuroinflammation and dopaminergic cell loss, but the prime cause of those events is still in debate.MethodsWe examined the neuropathological effects of PQ not only in substantia nigra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Previous studies have reported that PQ upregulates the levels of α-synuclein [8790,34]. We observed no effect of PQ on the total endogenous levels of α-synuclein in SK-N-SH dopaminergic cells ( data not shown ) or in PQ treated C57Bl/6 (Fig.…”
Section: Resultssupporting
confidence: 41%
“…Previous studies have reported that PQ upregulates the levels of α-synuclein [8790,34]. We observed no effect of PQ on the total endogenous levels of α-synuclein in SK-N-SH dopaminergic cells ( data not shown ) or in PQ treated C57Bl/6 (Fig.…”
Section: Resultssupporting
confidence: 41%
“…Other studies have shown that high-cholesterol diets can induce neuroinflammation in the hippocampus, but not in the cortex (Xue et al, 2007), and that Paraquat, a herbicide which can cause neurotoxicty, can induce different brain region expression of pro-inflammatory cytokines and neuroinflammation in the hippocampus (Mitra et al, 2011). These findings, together with the data from our current study, suggest that the hippocampus could be more susceptible to inflammation insult.…”
Section: Discussionmentioning
confidence: 99%
“…Although paraquat preferentially affects the nigrostriatum system, it also accumulates in cerebral cortex and hippocampus, brain regions important for cognition (Prasad et al, 2009). Systemic exposure of paraquat was shown to result in pathological changes in hippocampus and cortex, and induced nonmotor symptoms, such as an increase in anxiety-like behavior and dysfunction in nonsocial olfactory discrimination (Czerniczyniec et al, 2011;Mitra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%